Advances in Self-Organizing Maps 8th International Workshop, WSOM 2011, Espoo, Finland, June 13-15, 2011. Proceedings - Laaksonen, Jorma; Honkela, Timo.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 8th International Workshop on Self-Organizing Maps, WSOM 2011, held in Espoo, Finland, in June 2011. The 36 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on plenaries; financial and societal applications; theory and methodology; applications of data mining and analysis; language processing and document analysis; and visualization and image processing.
Keywords: Computer science; Database management; Artificial intelligence; Computer vision; Optical pattern recognition; Computer aided design; Computer Science; Computation by Abstract Devices; Artificial Intelligence (incl. Robotics).; Database Management; Image Processing and Computer Vision; Pattern Recognition; Computer-Aided Engineering (CAD, CAE) and Design